A review of the treatment of drug induced presbyopia - Srivastava, Namrata; Dwivedi, P. N.; Chaurasia, Vikas Kumar (International Journal Of Community Medicine And Public Health, 2023)
Presbyopia is characterized by accommodative loss that leads to negative effects on vision-targeted health-related quality of life. It occurs in people who gradually lose the ability to adapt after the age of 40. Accommodation depends on the contraction of the ciliary muscle and the iris, the change and the convergence of the lens. The parasympathetic nervous system regulates the degree of contraction of the ciliary muscle and the iris necessary to alter the shape and position of the lens, and its stimulation is effective by activating the muscarinic receptors present in both structures. The hypothesis presented here suggests that patients with emmetropic presbyopia correct accommodation with pharmacotherapy that includes a combination of cholinergic drugs and non-steroidal anti-inflammatory drugs (NSAIDs). Topical treatment deals with drug combinations to modify one or more factors involved in the accommodative process and have been proposed to be instilled either monocular/ binocularly. Result shows para-sympathomimetic stimulation of parasympathetic innervation (accommodation) and NSAID: Prolonging the effect of the para-sympathomimetic action and modulates the accommodation. The drug combination restores near vision without affecting distance vision. It is important to note that the drug form used has no inflammatory effects or other side effects. Despite the lack of a completely well understood mechanism, pharmacological control of presbyopia seems to be a possible and very attractive alternative for presbyopia patients. The studies mentioned in this review are to be considered pilot investigations as they involve either a small number of subjects or are single case series.